2013
DOI: 10.5249/jivr.v5i2.303
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of intra-articular morphine after arthroscopic knee surgery in sport injury patients

Abstract: Abstract:Background:Anterior Cruciate Ligament (ACL) tearing is a common injury among football players. The present study aims to determine the best single-dose of intra-articular morphine for pain relief after arthroscopic knee surgery that, in addition to adequate and long-term analgesia, leads to fewer systemic side effects. Methods:This clinical trial was conducted on 40 ASA-I athletes. After surgery, all participants received an injection of 20cc of 0.5% intra-articular bupivacaine. In addition, the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
(5 reference statements)
0
22
0
2
Order By: Relevance
“…In a study by Yari et al ., 40 patients undergoing anterior cruciate ligament repair were recruited and divided into four groups. [ 11 ] All the patients received 20 cc of 0.5% IA bupivacaine with either NS, 5 mg, 10 mg or 15 mg morphine. The authors observed that 15 mg IA morphine with 20 cc of 0.5% bupivacaine increased the analgesia level as well as its duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Yari et al ., 40 patients undergoing anterior cruciate ligament repair were recruited and divided into four groups. [ 11 ] All the patients received 20 cc of 0.5% IA bupivacaine with either NS, 5 mg, 10 mg or 15 mg morphine. The authors observed that 15 mg IA morphine with 20 cc of 0.5% bupivacaine increased the analgesia level as well as its duration.…”
Section: Discussionmentioning
confidence: 99%
“…Variable doses of IA morphine, ranging from 1 to 10 mg, have been used in various published clinical trials. [ 7 8 9 10 11 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…16 Third, several trials found the effectiveness of peripheral opioid injections for local analgesia, such as intra-articular morphine after knee surgery. 17,18 Local opioid analgesic actions are pronounced in inflamed tissues. This may be attributed to the increased number of exposed opioid receptors and/or increased coupling with G-proteins (the degradation of perineural barriers and passage of agonists results in exposure of opioid receptors).…”
Section: Enrollmentmentioning
confidence: 99%
“…Desde que se realiza la artroscopía de rodilla con anestesia local (3) , el resto de las técnicas anestésicas se han utilizado menos, pues el control del dolor intra y postoperatorio son suficientes y las complicaciones escasas (28) .…”
Section: Wwwmedigraphicorgmxunclassified
“…Yari y colegas (28) determinaron la mejor dosis única de morfina intraarticular para aliviar el dolor postcirugía artroscópica de rodilla y determinar la mejor analgesia a largo plazo, con menos efectos secundarios sistémicos. Para ello, administraron en 40 atletas ASA-I (después del procedimiento quirúrgico) una inyección de 20 mL de 0.5% intraarticular de bupivacaína con 5, 10 y 15 mg de morfina.…”
Section: Osteoartritisunclassified